Screen‐detected and interval colorectal cancers in England: Associations with lifestyle and other factors in women in a large UK prospective cohort - Blanks, R; Pust, A; Alison, R; He, E; Barnes, I; Patnick, J; Reeves, G; Floud, S; Beral, V; Green, J (Wiley, 2019)
Faecal occult blood (FOB) ‐ based screening programmes for colorectal cancer detect about half of all cancers. Little is known about individual health behavioural characteristics which may be associated with screen‐detected and interval cancers. Electronic linkage between the UK National Health Service Bowel Cancer Screening Programme (BCSP) in England, cancer registration and other national health records, and a large on‐going UK cohort, the Million Women Study, provided data on 628,976 women screened using a guaiac‐FOB test (gFOBt) between 2006 and 2012. Relative risks (RRs) and 95% confidence intervals (CIs) were estimated by logistic and Cox regression for associations between individual lifestyle factors and risk of colorectal tumours. Among screened women, 766 were diagnosed with screen‐detected colorectal cancer registered within 2 years after a positive gFOBt result, and 749 with interval colorectal cancers registered within 2 years after a negative gFOBt result. Current smoking was significantly associated with risk of interval cancer (RR 1.64, 95%CI 1.35–1.99) but not with risk of screen‐detected cancer (RR 1.03, 0.84–1.28), and was the only factor of eight examined to show a significant difference in risk between interval and screen‐detected cancers (p for difference, 0.003). Compared to screen‐detected cancers, interval cancers tended to be sited in the proximal colon or rectum, to be of non‐adenocarcinoma morphology, and to be of higher stage.